Eko Aditya Rifai (1989-2021): An outstanding Indonesian young scientist on bioinformatics - Rukmana, Taufiq Indra (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2021)
An outstanding Indonesian young scientist on bioinformatics